Spin transport in magnetic nanostructures - Boldoba, Oscar Céspedes (Trinity College (Dublin, Ireland). School of Physics, 2005)
The study presented in this thesis is concerned with the spin dependent transport and spin transfer in magnetic nanostructures. The first two chapters are dedicated to introduce spin-electronics, electrical transport and the experimental techniques commonly used in this work. Chapters three and four present the results obtained in the measurement of electronic transport in Ni, Fe3 04 (magnetite) and (Lao.7 Sro.3) Mn03 (LSMO) nanostructures. The idea examined in chapter five is to place a multi-walled carbon nanotube (MWCNT) in contact with a ferromagnet and measure the spin transfer associated with the alignment of their chemical potentials. In chapter six the results obtained will be discussed and chapter seven contains the conclusion and proposed further work.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin